PROPOSAL OF A MODEL FOR STRENGTHENING SCIENTIFIC PRODUCTIVITY AT THE UNIVERSITY LEVEL - Daher, Jorge; Panunzio, Amelia Patricia; Navarro, Marlene Hernández (International Journal of Research -GRANTHAALAYAH, 2020)
The proposal to strengthen scientific production at the university level has dimensions, components and characteristics and a structure designed based on the theoretical contributions of this research and the results obtained in each objective addressed, considering that scientific research is an indicator of the quality of the processes in the university environment, so it must be increased by virtue of the results of the work carried out by the research professors and students.